Behavior of tropical forage legumes under different fertilization in Petrolina, Pernambuco, Brazil - Silva, Célia M. Maganhotto de S.; Faria, Clementino M. B. de (Pesquisa Agropecuaria Brasileira, 2014)
This study evaluated the yield of twelve forage legumes, with and without phosphorus fertilization. The selected species were planted in 6m x 3m plots, with a spacing of 0.60 m between lines. The experimental design was in randomized blocks divided in sub-plots with three replications. Species were the main plots and fertilization levels (0 and 60 kg of P2O5) were the sub-plots. The species Macroptilium sp CPATSA 80218 (BRA-004537) and Indigofera sp CPATSA 7620 (BRA-000701) showed the best results during the 3-year study, producing averages of 5,430 and 4,862; 3,972 and 3,736 kg of dry matter/ha/year with and without phosphorus fertilization, respectively. Although the phosphorus level in the soil was low, the species tested showed a low (9%) response to phosphorus fertilization.
Keywords: phosphorus; yield; crud protein